The influence of geomorphology and sedimentary processes on shallowwater benthic habitat distribution: Esperance Bay, Western Australia - Ryan, D.; Brooke, B.; Collins, Lindsay; Kendrick, G.; Baxter, K.; Bickers, A.; Siwabessy, Paulus; Pattiaratchi, C. (Elsevier, 2006)
The mapping of seabed environments is fundamental to successful fisheries management and environmental monitoring, however, there is an emerging need to better characterise habitats based upon appropriate physical parameters. In this study, relationships between seabed geomorphology and the distribution of benthic habitats were examined using multibeam sonar, underwater video, predicted wave energy, and sediment data for Esperance Bay, part of the Recherche Archipelago. This shallow (<50 m), high energy, biogenic sediment dominated environment is located in temperate southwestern Australia. Exposure to wave energy appears to determine the distribution of unconsolidated substrate, and is the most useful regional scale predictor of rhodolith and seagrass habitats. Although they are intermittently smothered by mobile sediments, limestone reefs provide habitat for a wide range of sessile organisms, even in very high wave exposure environments. The distribution of rhodolith beds is related to poorly sorted sediments that contain high gravel, mud, and CaCO3 percentages. Our results reveal that in the Recherche Archipelago, wave abrasion coupled with localised sediment transport and accumulation play a major role in increasing the diversity of inner shelf benthic habitats. This highlights the value of assessing geomorphic processes in order to better understand the distribution and structure of benthic habitats.